Lactic Acid Level as A Predictor of Severity in Patients with Acute Appendicitis - Aditya, Raka; Rudiman, Reno; Hapsari, Putie (Faculty of Medicine, Universitas Padjadjaran, 2024)
Perforated appendicitis is the leading cause of morbidity and mortality of all appendicitis cases in adults and children, with delayed preoperative diagnosis as the main reason. In previous studies, diagnostic modalities such as radiological examination and the current scoring system have been demonstrated as unable to predict the onset of perforated appendicitis. Serological biomarkers of lactic acid are associated with intestinal obstruction and ischemia. The serological value of lactic acid in identifying perforated appendicitis compared to acute one was shown to increase significantly by 0.25 mmol/L (p<0.05) in a previous study. This study aimed to determine the correlation between lactic acid and the severity of appendicitis. This was a cross-sectional prospective analytic observational study in patients treated in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Subjects were adult patients diagnosed with appendicitis during the period of 2021 in the Emergency Room of the hospital. Data were analyzed using the bivariate analysis and correlation test of difference. This study involved 54 subjects, divided into the complicated appendicitis (study) and control groups, with a mean of lactic acid level of 2,5093 mmol/L (0.9 mmol/L–11.8 mmol/L). In the complicated appendicitis group, 20 subjects (37%) demonstrated an increase in lactic acid level (OR 1.07; 95% CI: -0.03–0.22; p=0.14). The correlation analysis resulted in a negative correlation. This study concluded that there is no significant correlation between lactic acid levels and the severity of appendicitis in these patients.